The Influence of Chinese Travel Applications Content Marketing on Chinese Users’ Travel Decisions to Bangkok, Thailand - Wang, Rui (ASEAN Journal of Management & Innovation, 2025)
This research aimed 1)to study the influence of Chinese travel applications content marketing on Chinese people's travel decisions in Bangkok, Thailand 2) to study the influence of travel applications on users' perception from three dimensions: information, price and feedback 3) to study the influence of users' perception on users' travel decisions from three dimensions: destination image perception, perceived value and perceived trust and 4) to study the mediating effects of perception of users on the relationship between content marketing and decision making. The sample group was Chinese people who have already been in Bangkok and have used at least one Chinese travel application. Select samples by snowball sampling method. The instruments used were questionnaire star to distribute and collect data. The statistics used were Amos statistics processing tool. The research results were found as follows:1)The information and feedback on travel applications have significant effect on users’ perceptions and users’ travel decision. 2) The destination image perception, perceived value and perceived trust have significant effect on users’ travel decision. And 3)The price on travel applications doesn’t have significant effect on users’ perceptions and users’ travel decision.4)It was found that the effect of user perception on the relationship between content marketing and decision making was only partially significant.